The gut in iron homeostasis: role of HIF-2 under normal and pathological conditions - Mastrogiannaki, Maria (American Society of Hematology, 2013)
Although earlier, seminal studies demonstrated that the gut per se has the intrinsic ability to regulate the rates of iron absorption, the spotlight in the past decade has been placed on the systemic regulation of iron homeostasis by the hepatic hormone hepcidin and the molecular mechanisms that regulate its expression. Recently, however, attention has returned to the gut based on the finding that hypoxia inducible factor-2 (HIF-2α) regulates the expression of key genes that contribute to iron absorption. Here we review the current understanding of the molecular mechanisms that regulate iron homeostasis in the gut by focusing on the role of HIF-2 under physiological steady-state conditions and in the pathogenesis of iron-related diseases. We also discuss implications for adapting HIF-2–based therapeutic strategies in iron-related pathological conditions.